PENGORGANISASIAN SUPERVISI PENDIDIKAN ISLAM, DEEP LEARNING, KURIKULUM BERBASIS CINTA, DAN PENGEMBANGAN MATERI AJAR PADA SEKOLAH DASAR - Asad Zamiko; Ahmad Zainuri (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
Islamic education at the elementary school level plays a fundamental role in building the foundation of faith, developing noble morals, and developing students' intellectual, emotional, and social intelligence. The dynamics of global development, marked by technological advances, changes in generational character, and the complexity of educational challenges, demand innovation in the management of Islamic Religious Education learning. This article aims to critically and systematically examine the organization of Islamic education supervision by integrating a deep learning approach and a love-based curriculum in the development of teaching materials in elementary schools. This research uses a descriptive qualitative approach through a literature review of various scientific sources, including books, national and international journal articles, and educational policy documents. The results of the study indicate that structured Islamic education supervision can improve teacher professionalism in designing meaningful learning. The deep learning approach contributes to strengthening students' conceptual and reflective understanding, while the love-based curriculum instills the values ​​of compassion, empathy, and Islamic character. The integration of these three aspects results in the development of teaching materials that are holistic, contextual, and relevant to the needs of elementary school students.